Dinamika Modal Sosial dalam Meningkatkan Kesejahteraan: Studi Kasus di GPdI Ekklesia Prambon - Glory Stephanie Rebbeca Mewengkang; Dewien Nabielah Agustin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study is motivated by the persistently high level of socio-economic vulnerability among impoverished congregations and the strategic importance of the church as a religious institution that functions not only spiritually but also socially in fostering community-based welfare. The research aims to explore the meaning of the church’s role from the perspective of economically disadvantaged congregants and to analyze the dynamics of social capital that contribute to the improvement of their well-being. The study was conducted at GPdI Ekklesia Prambon in Sidoarjo Regency using a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed using the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that congregants perceive well-being in a multidimensional manner, encompassing physical, spiritual, social, and relational aspects. The church plays a significant role through participatory programs such as basic food assistance, educational support, prayer services, and social accompaniment. The dynamics of social capital are reflected in mutual trust, norms of solidarity, and strong social networks, which collectively foster social resilience and promote sustainable congregational well-being.